2022
DOI: 10.1016/j.jtcvs.2020.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for ischemic mitral regurgitation: A meta-analysis

Abstract: Background. Treatment of ischemic mitral regurgitation (IMR) is in evolution as percutaneous procedures and complex surgical repair have been recently investigated in randomized clinical trials and matched studies. This study aims to review and compare the current treatment options for IMR.Methods. A comprehensive literature search was conducted using electronic databases. The primary outcome was all-cause long-term mortality. The secondary outcomes were perioperative mortality, unplanned rehospitalization, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 52 publications
1
66
0
Order By: Relevance
“…Numerous studies have focused on the degree of annular restriction by mitral annuloplasty given the reported risk of stenosis, systolic anterior motion, and recurrent MR in overcorrection or excessive undersizing. [1][2][3][4][5][6][7][8][9] The anterior leaflet enlargement patch as performed by the authors is progressive 10 (Figure 1), provided that there is a marked reduction of tethering forces. 11,12 The forces on the fibrous skeleton of the heart exerted by annular undersizing would counteract the displacement vectors relative to the LV dilation expected in these patients.…”
Section: A Right Track Stems From the Right Learning To The Editormentioning
confidence: 99%
“…Numerous studies have focused on the degree of annular restriction by mitral annuloplasty given the reported risk of stenosis, systolic anterior motion, and recurrent MR in overcorrection or excessive undersizing. [1][2][3][4][5][6][7][8][9] The anterior leaflet enlargement patch as performed by the authors is progressive 10 (Figure 1), provided that there is a marked reduction of tethering forces. 11,12 The forces on the fibrous skeleton of the heart exerted by annular undersizing would counteract the displacement vectors relative to the LV dilation expected in these patients.…”
Section: A Right Track Stems From the Right Learning To The Editormentioning
confidence: 99%
“…37 Intriguingly, an examination of the baseline characteristics of the patients participating in the 2 trials indicated that the studies included 2 distinctly different populations of patients with FMR. 45,46 Patients enrolled in the COAPT trial had more severe FMR (EROA 41mm 2 vs. 31mm 2 ; RVol 60ml vs. 45ml) and less dilated ventricles (LVEDV index 101ml/m 2 vs. 135ml/m 2 ) than those in the MITRA-FR trial. According to the concepts of proportionate and disproportionate MR, it is evident that the patients in the MITRA-FR trial represent a population in which the MR is proportional to the ventricular dilatation and is a consequence, not a cause, of the ventricular disease.…”
Section: Pathophysiology Of Fmr: An Evolving Conceptual Frameworkmentioning
confidence: 99%
“…To address this question, Nappi and colleagues 6 have conducted a timely meta-analysis. Along with analyzing the available surgical trials, their comprehensive systematic review also covers several important aspects, including rapidly-evolving transcatheter therapy-namely, the MitraClip intervention-and the latest clinical evidence on guideline-directed medical therapy.…”
mentioning
confidence: 99%
“…On the one hand, we recognize that patients who had severe IMR following successful downsized annuloplasty (ie, without recurrence of MR) had the best clinical outcomes. 1,3,6 The well-proven principle "good repair is always better than good replacement" remains valid. Thus, restrictive annuloplasty as a useful tool could still be applied in some carefully selected patients.…”
mentioning
confidence: 99%